Analisis Konflik Batin Tokoh Utama Rani Dalam Cerpen Saat Mas Ingin Menikah Lagi Karya Nirmala Rustini - Muhammad Rizqi Darmawan; Bima Tirta Wijaya; Eva Dwi Kurniawan (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research aims to describe the form of inner conflict of the main character Rani in the short story Saat Mas Wants to Marry Again by Nirmala Rustini. The problem in this research is more focused on the form of inner conflict of the main character Rani. The method used in this research is a qualitative descriptive method, using a short story literary work entitled When Mas Wants to Marry Again by Nirmala Rustini as a research source. The data collection technique uses the note-reading method, by reading the entire short story and recording relevant data to be used as a source of research data. From the results of this research, it was found that there were five inner conflicts found in the short story When Mas Wants to Marry Again, namely feelings of sadness, feelings of anger, feelings of fear, feelings of anxiety, and feelings of disappointment.